Efficiency of bio-stimulant combined with mechanical scarification on germination of flamboyant seeds (Research, Society and Development, 2024)
This study aimed to evaluate the effect of different concentrations of the bio-stimulant Stimulate® on overcoming dormancy, germination, and development of flamboyant seedlings (Delonix regia). Concentrations of Stimulate® used were 2.5; 5.0; 7.5; and 10.0 ml L-1, with seeds soaked for one hour. The seeds tested included those with intact teguments and those scarified with water sandpaper No. 120 on the side opposite the embryo, following a 5x2 factorial scheme. The treatments were arranged in a completely randomized design, with seeds sown in tubes containing commercial substrate. The results showed a significant interaction (p